A history of Western philosophy and theology - Frame, John M., 1939- (Phillipsburg, New Jersey : P & R Publishing, 2015)
Christians should evaluate philosophy by biblical criteria. This will shed greater light on the developments in the history of philosophy and better prepare us for the intellectual challenges of our time. The fall of Adam brought intellectual as well as moral corruption on the human race, and the effects of the fall can be seen in the work of philosophers, most of whom try to understand the world autonomously -- through reasoning apart from God's revelation. Some philosophers have appealed to God's revelation, but their work has often been compromised with the wisdom of the world. Revelation should inform reason, and not the other way round. In the past, even Christian theology was corrupted by the movement toward intellectual autonomy, creating the tradition of liberalism, which has unhappily dominated academic theology down to the present day. But there is hope -- a new generation of Christian thinkers take God's Word seriously.
Philosophy and the Bible -- Greek philosophy -- Early Christian philosophy -- Medieval philosophy -- Early modern thought -- Theology in the Enlightenment -- Kant and his successors -- Nineteenth-century theology -- Nietzche, pragmatism, phenomenology, and existentialism -- Twentieth-century liberal theology, part 1 -- Twentieth-century liberal theology, part 2 -- Twentieth-century language philosophy -- Recent Christian philosophy.
Includes bibliographical references (pages 789-829) and index.
Keywords: Christian philosophy -- History; Theology -- History